2017
DOI: 10.1002/masy.201700040
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and Microscopic Heterogeneity of Poly(ethylene oxide) Solid Polymer Electrolytes

Abstract: Lack of precise thermal control in poly(ethylene oxide) (PEO)‐based solid polymer electrolytes (SPEs) with molar masses well above M > 104 g mol−1 during preparatory stage often demonstrates molar mass dependence on thermal properties and ionic conductivities. In the earlier study, PEO‐based SPEs were heated under inert atmosphere above the melting temperature of PEO and then cooled down for subsequent isothermal crystallization. The system demonstrates insignificant variation with respect to molar mass of PEO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This observation is in agreement with the deviation in the power law for G′ . The observation for PEO in this study is in agreement with reported work (PEO, M η = 300 000 g mol −1 , T g = −58 °C, at 80 °C; 86 PEO, M η = 300 000 g mol −1 , T g = −58 °C, at 140 °C; 54 and PEO, M w = 932 000 g mol −1 and 610 000 g mol −1 measured at T = 105 and 75 °C, respectively 87 ). Additionally, work on the light scattering technique has also reported on the heterogeneity of molten PEO on a microscopic scale due to the structured random network formed by extensive inter‐ and intra‐polymers 12,88 .…”
Section: Resultssupporting
confidence: 93%
“…This observation is in agreement with the deviation in the power law for G′ . The observation for PEO in this study is in agreement with reported work (PEO, M η = 300 000 g mol −1 , T g = −58 °C, at 80 °C; 86 PEO, M η = 300 000 g mol −1 , T g = −58 °C, at 140 °C; 54 and PEO, M w = 932 000 g mol −1 and 610 000 g mol −1 measured at T = 105 and 75 °C, respectively 87 ). Additionally, work on the light scattering technique has also reported on the heterogeneity of molten PEO on a microscopic scale due to the structured random network formed by extensive inter‐ and intra‐polymers 12,88 .…”
Section: Resultssupporting
confidence: 93%
“…This observation is in agreement with light scattering studies reported by Walter et al [6] and Walkenhorst et al [41], where they observed the PEO melt was not uniform on the microscopic scale due to the structured random network formed by extensive inter-and intrapolymer connections. A rheological study on PEO (M w = 300,000 g•mol −1 ; T g = −57 • C) measured at T = 80 • C also reported deviations in both G and G from terminal viscoelastic relaxation, which indicated the restrictions of the long-range motion of PEO (data are listed in Table 2) [42]. Furthermore, the heterogeneities of PEO can also be observed using impedance spectroscopy at 25 • C by adding very low salt concentrations (e.g., 0.05 wt %) due to the formation of a percolation network of conductive (polymer-poor) and dielectric (polymer-rich) domains [10].…”
Section: Rheological Properties Of the Parent Polymersmentioning
confidence: 98%
“…Rheological behavior of PEO is accordingly tuned by the content of salts. Harun et al [71] studied the calorimetry and rheology of PEO-lithium salt mixtures. They found T g increases with salt content, and the terminal relaxation is extended and broadened.…”
Section: Linear Viscoelasticitymentioning
confidence: 99%